The Development of Mathematics E-Module Based on Problem Based Learning using Flip PDF Professional - Fuziani, Meilidya; Wafiqoh, Risnina; Agustine, Putri Cahyani (Pelangi (e-Journal), 2025)
This research is motivated by the limitations of teachers who have not implemented teaching materials in schools, the lack of mathematics word problems related to everyday life issues, and using conventional methods in class resulting in low students' problem-solving abilities. This study was conducted to determine the characteristics of mathematics e-modules based on problem-based learning using the flip pdf professional application on valid and practical Matrix and to determine its potential effects. This research is a research and development with a 4D (four D) development model consisting of four stages, they are Define, Design, Develop, and Disseminate. This study develops a mathematics e-module based on problem-based learning using the flip pdf professional application on valid matrix with an average validity score of 98.89% including the criteria of "very valid" and practical with an average practicality score of 89.03% including the criteria of "very practical. The characteristics developed are the existence of questions related to the competency of the department and the stages of work using the steps of the problem-based learning model. E-modules also have a potential effect of 0.74 on students' problem-solving abilities, which can potentially improve understanding and problem-solving abilities in mathematics.